Clinical significance of esophageal invasion length for the prediction of mediastinal lymph node metastasis in Siewert type II adenocarcinoma: A retrospective single‐institution study. Issue 3 (10th April 2018) - Koyanagi, Kazuo; Kato, Fumihiko; Kanamori, Jun; Daiko, Hiroyuki; Ozawa, Soji; Tachimori, Yuji
Abstract: Aim: This study investigated whether esophageal invasion length (EIL) of a tumor from the esophagogastric junction could be a possible indicator of mediastinal lymph node metastasis and survival in patients with Siewert type II adenocarcinoma. Methods: One hundred and sixty‐eight patients with Siewert type II tumor who underwent surgery were enrolled. Metastatic stations and recurrent lymph node sites were classified into cervical, upper/middle/lower mediastinal, and abdominal zones. EIL was correlated with overall metastasis or recurrence in individual zones and with survival. Results: Siewert type II patients with an EIL of more than 25 mm (>25 mm EIL group) had a higher incidence of overall metastasis or recurrence in the upper and middle mediastinal zones than those with an EIL of less than or equal to 25 mm (≤25 mm EIL group) ( P = .001 and P < .001). Disease‐free and overall survival in the >25 mm EIL group were significantly lower than those of the ≤25 mm EIL group ( P < .001). None of the Siewert type II patients with metastasis or recurrence in the upper and middle mediastinal zones survived for more than 5 years. Only an EIL of more than 25 mm was a significant preoperative predictor of overall metastasis or recurrence in the upper and middle mediastinal zones (odds ratio, 8.85; 95% CI, 2.31‐33.3; P = .001). Conclusion: A multimodal‐therapeutic strategy should be investigated in Siewert type II patients once the tumor has invaded more than 25 mm to the esophageal wall. Abstract : The present study indicated that overall metastasis or recurrence in the upper and middle mediastinal zones is associated with esophageal invasion length (EIL) in patients with Siewert type II tumors, and an EIL of more than 25 mm might be a preoperative predictor of overall metastasis or recurrence in the upper and middle mediastinal zones. Overall survival rate in the >25 mm EIL group was significantly lower than that of the ≤25 mm EIL group.